Development of a Physiologically‐Based Pharmacokinetic Model for Sirolimus: Predicting Bioavailability Based on Intestinal CYP3A Content. (24th July 2013) - Emoto, C; Fukuda, T; Cox, S; Christians, U; Vinks, AA
Abstract : Sirolimus is an inhibitor of mammalian target of rapamycin (mTOR) and is increasingly being used in transplantation and cancer therapies. Sirolimus has low oral bioavailability and exhibits large pharmacokinetic variability. The underlying mechanisms for this variability have not been explored to a large extent. Sirolimus metabolism was characterized by in vitro intrinsic clearance estimation. Pathway contribution ranked from CYP3A4 > CYP3A5 > CYP2C8. With the well stirred and Qgut models sirolimus bioavailability was predicted at 15%. Interindividual differences in bioavailability could be attributed to variable intestinal CYP3A expression. The physiologically‐based pharmacokinetics (PBPK) model developed in Simcyp predicted a high distribution of sirolimus into adipose tissue and another elimination pathway in addition to CYP‐mediated metabolism. PBPK model predictive performance was acceptable with C max and area under the curve (AUC) estimates within 20% of observed data in a dose escalation study. The model also showed potential to assess the impact of hepatic impairment and drug–drug interaction (DDI) on sirolimus pharmacokinetics. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e59; doi:10.1038/psp.2013.33 ; published online 24 July 2013